New technologies, new tools, new organisation of the city: Towards a new digital planning? - Nicolas Douay; Christian Lamker (Cities and metropolises in France and Germany, 2022)
A full digital transformation is unfolding and great hopes are vested in the potentials of digital tools for communication and visualisation in planning processes, for analysing and modelling spatial information, and also for managing whole cities and regions. However, actual practices differ vastly, and the debate increasingly points to the pitfalls and dangers of a disconnect between citizens, spatial justice and democratic decision making. Examples of smart cities show a huge variety of interpretations and implementations in Europe. Therefore, digital tools should not become a goal in themselves, but need a clear societal and spatial vision and open political debates. This chapter looks at digital technologies in spatial planning as an increasingly political agenda in France and in Germany. In many regards, both countries must deal with similar opportunities and challenges posed by digital technologies, companies and global platforms. These are mediated differently through national political and planning systems and a more centralised approach in France versus a muchdecentralised agenda in Germany.
urn:nbn:de:0156-1119098; hdl:10419/266400; https://econpapers.repec.org/RePEc:zbw:arlfob:20
Keywords: 710; Digitalisation; smart city; France; Germany; technology; role of planners